Performance of Drip and Mist Irrigation to Supply Water for Vegetable - Murtiningrum, Murtiningrum; Rasyid, Ilham Nawan; Christyaningrum, Lia; Fahrunisa, Erlina; Ngadisih, Ngadisih (IOP Publishing Ltd, 2022)
Irrigation or water use for agriculture is the biggest water consumer. Reducing water use for irrigation means significantly to water saving. Drip and mist irrigations are methods of water application which consume water more efficiently and more agriculture products produce from same amount of water. This research aimed to assess performance off drip irrigation and mist irrigation to supply irrigation water for vegetables. The vegetables cultivated were spinach, mustard, and water spinach. The indicators employed were discharge, uniformity, dan water productivity. The research results showed that average discharges of drip and mist irrigations were 0.0056 litre/second and 0.0012 litre/second, respectively. The uniformity was measured using distribution uniformity (DU) and Christiansen uniformity index (CU). The DU of drip and mist irrigations were 0.84 and 0.76, respectively. The CU of drip and mist irrigations were 0.76 and 0.82, respectively. The biomass water productivities of spinach, mustard, and water spinach irrigated with drip irrigation were 2.23, 9.51, and 7.92, respectively. The biomass water productivities of spinach, mustard, and water spinach irrigated with mist irrigation were 0.98, 8.70, and 9.10, respectively.